2x+9 \(⋮\) x+1
Ta có : 2x+9 = 2(x+1)+7
Mà 2(x+1) \(⋮\) x+1
để 2x+9 \(⋮\) x+1 thì => 7 \(⋮\) x+1 hay x+1 \(\in\) Ư (7 )
Ư(7) ={1;7 }
Ta có bảng sau
x+1 | 1 | 7 |
x | 0 | 6 |
Vậy x\(\in\) {0;6}
\(2x+9⋮x+1\Leftrightarrow2\left(x+1\right)+7⋮x+1\Leftrightarrow7⋮x+1\)
hay \(x+1\inƯ\left(7\right)=\left\{1;7\right\}\)
x + 1 | 1 | 7 |
x | 0 | 6 |
Vì ( x + 1 ) \(⋮\)( x + 1 ) \(\Rightarrow\)( 2x + 9 ) : ( x + 1 )
\(\Rightarrow\)( 2x + 9 ) - ( x + 1 ) : ( x + 1 )
\(\Rightarrow\)( 2x + 9 ) - 2.( x + 1 ) : ( x + 1 )
\(\Rightarrow\)( 2x + 9 ) - ( 2x + 2 ) : ( x + 1 )
\(\Rightarrow\)7 : ( x + 1 )
\(\Rightarrow\)x + 1 \(\in\)Ư ( 7 )
\(\Rightarrow\)x + 1 = { 1,7 }
TH1:
x + 1 = 1
x = 1 - 1
x = 0
TH2 :
x + 1 = 7
x = 7 - 1
x = 6
Vậy x = 0 và 1